Penguatan Implementasi Kurikulum Merdeka di Sekolah/Madrasah melalui Bimtek Model In-On-In - Agus Salim Chamidi; Nurhidayah Nurhidayah; Agoes Dariyo; Dian Hidayati; Fuad Aljihad; Millah Kamilah Muslimat; Muhammad Akasah; Irvan Kristivan; Agus Mulyanto; Okke Rosmaladewi (Dikmas: Jurnal Pendidikan Masyarakat dan Pengabdian, 2022)
The Implementation of the Independent Curriculum (IIC) rolled out by the government is enough to cause stuttering in the school/madrasah environment, especially for teachers. The purpose of this community service research is to increase the understanding and mastery of the IIC for teachers and school/madrasah principals. The method used is the in-on-in learning model with the packaging of technical guidance which is organized by involving the multistakeholders. The results are: (1)technical guidance is able to uncover a number of deadlocks in IKM, so that the stuttering and worries that arise can turn into increased understanding and mastery of IKM, KOSP, and MA, (2)technical guidance is even able to present a solution to improve the quality of education related to the preparation of the KOSP and MA, (3)technical guidance shows a significant increase in understanding and mastery of IKM, KOSP, and MA, and (4)the implementation of the IKM technical guidance has a positive influence on the performance of the collaborating parties. The recommendation is that the in-on-in model by collaborating with a number of schools/madrasahs, university, and other institutions should continue to be carried out to increase understanding and mastery of IKM, as well as to improve the performance of the stakeholders.Implementasi Kurikulum Merdeka (IKM) yang digulirkan pemerintah cukup menimbulkan kegagapan di lingkungan sekolah/madrasah, khususnya bagi para guru. Tujuan penelitian pengabdian masyarakat ini adalah untuk meningkatkan pemahaman dan penguasaan IKM bagi guru dan kepala sekolah/madrasah. Metode yang digunakan adalah model pembelajaran in-on-in dengan kemasan bimbingan teknis (bimtek) yang diselenggarakan dengan melibatkan multistakeholders. Hasil pengabdian adalah: (1)bimtek mampu menguak sejumlah kebuntuan dalam IKM, sehingga kegagapan dan kekhawatiran yang timbul mampu berubah menjadi peningkatan pemahaman dan penguasaan IKM, KOSP, dan MA, (2)bimtek bahkan mampu menyuguhkan sebentuk solusi perbaikan mutu pendidikan terkait penyusunan KOSP dan MA, (3)bimtek menunjukkan terjadi peningkatan pemahaman dan penguasaan IKM, KOSP, dan MA yang signifikan, dan (4)penyelenggaraan bimtek IKM ternyata mempunyai pengaruh positif pada kinerja para pihak yang berkolaborasi. Rekomendasinya, model in-on-in dengan mengkolaborasikan sejumlah sekolah/madrasah, perguruan tinggi (PT), dan lembaga lain layak terus dilakukan untuk peningkatan pemahaman dan penguasaan IKM, sekaligus untuk peningkatan kinerja para pihak.